2012
DOI: 10.1161/circulationaha.111.066092
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocytes Derived From Pluripotent Stem Cells Recapitulate Electrophysiological Characteristics of an Overlap Syndrome of Cardiac Sodium Channel Disease

Abstract: Background-Pluripotent stem cells (PSCs) offer a new paradigm for modeling genetic cardiac diseases, but it is unclear whether mouse and human PSCs can truly model both gain-and loss-of-function genetic disorders affecting the Na ϩ current (I Na ) because of the immaturity of the PSC-derived cardiomyocytes. To address this issue, we generated multiple PSC lines containing a Na ϩ channel mutation causing a cardiac Na ϩ channel overlap syndrome. Method and Results-Induced PSC (iPSC) lines were generated from mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
187
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(207 citation statements)
references
References 42 publications
17
187
1
2
Order By: Relevance
“…The green area defines the normal QT interval range for humans. Data are shown as mean ± SD: 1, (Malan et al , 2016); 2, (Rocchetti/Sala et al , unpublished); 3, (Zhang et al , 2014); 4, (Zhang et al , 2014); 5, (Davis et al , 2012); 6, (Rocchetti/Sala et al , unpublished); 7, (Bellin et al , 2013); 8, (Sala et al , 2016); 9, (Bizy et al , 2013); 10, (Ma et al , 2013); 11, (Ma et al , 2015); 12, (Ma et al , 2015); 13, (Gibson et al , 2014a); 14, (Itzhaki et al , 2011); 15, (Gibson et al , 2014c); 16, (Lu et al , 2014); 17, (Gibson et al , 2014b); 18, (Mehta et al , 2014). (B) and (C) Composition of extracellular buffers (B) and pipette solutions (C) for current clamp experiments.…”
Section: Assays and Readoutsmentioning
confidence: 99%
“…The green area defines the normal QT interval range for humans. Data are shown as mean ± SD: 1, (Malan et al , 2016); 2, (Rocchetti/Sala et al , unpublished); 3, (Zhang et al , 2014); 4, (Zhang et al , 2014); 5, (Davis et al , 2012); 6, (Rocchetti/Sala et al , unpublished); 7, (Bellin et al , 2013); 8, (Sala et al , 2016); 9, (Bizy et al , 2013); 10, (Ma et al , 2013); 11, (Ma et al , 2015); 12, (Ma et al , 2015); 13, (Gibson et al , 2014a); 14, (Itzhaki et al , 2011); 15, (Gibson et al , 2014c); 16, (Lu et al , 2014); 17, (Gibson et al , 2014b); 18, (Mehta et al , 2014). (B) and (C) Composition of extracellular buffers (B) and pipette solutions (C) for current clamp experiments.…”
Section: Assays and Readoutsmentioning
confidence: 99%
“…Disease-specific iPSCs have also been generated from other heart diseases such as Brugada syndrome [45] , arrhythmogenic right ventricular cardiomyopathy [46] and catecholaminergic polymorphic ventricular tachycardia [47] (Table 1). Similar to the studies focused on neurological disorders, these studies not only support the use of the iPSC-derived cardiomyocytes to model the abnormal functional phenotype of inherited cardiac disorders in vitro but also demonstrate the possibility of using these cells to screen existing or experimental drugs.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…13,[62][63][64][65][66][67] Moretti et al first showed that patient-specific iPSC-derived cardiomyocytes could recapitulate the disease phenotype in congenital LQTS. 62) They generated iPScs from two patients with LQTS type 1, who had autosomal-dominant inheritance of a G569a missense mutation in the KCNQ1 gene encoding the IKs current which was previously shown to be relevant to LQTS onset by functional analysis of the mutated gene.…”
Section: Cardiovascular Disease Modeling Using Ipscsmentioning
confidence: 99%